Coronary Atherosclerotic Plaque Vulnerability Rather than Stenosis Predisposes to Non-ST Elevation Acute Coronary Syndromes - Mohamed Laimoud; Farouk Faris; Helmy Elghawaby (Cardiology Research and Practice)
Background. Non-ST elevation acute coronary syndromes (NSTE-ACS) may arise from moderately stenosed atherosclerotic lesions that suddenly undergo transformation to vulnerable plaques complicated by rupture and thrombosis. Objective. Assessment and tissue characterization of the coronary atherosclerotic lesions among NSTE-ACS patients compared to those with stable angina. Methodology. Evaluation of IVUS studies of 312 coronary lesions was done by 2 different experienced IVUS readers, 216 lesions in 66 patients with NSTE-ACS (group I) versus 96 lesions in 50 patients with stable angina (group II). Characterization of coronary plaques structure was done using colored-coded iMap technique. Results. The Syntax score was significantly higher in group I compared to group II (18.7 ± 7.8 vs. 8.07 ± 2.5, p=0.001). Body mass index (BMI) was significantly higher in group II while triglycerides levels were higher in group I (P=0.01 & P=0.04, respectively). History of previous MI and PCI was significantly higher in group I (P=0.016 & P=0.001, respectively). The coronary lesions of NSTE-ACS patients had less vessel area (9.86 ± 3.8 vs 11.36 ± 2.9, p=0.001), stenosis percentage (54.7 ± 14.9% vs 68.6 ± 8.7%, p=0.001), and plaque burden (54.4 ± 14.7 vs 67.8 ± 9.8, p=0.001) with negative remodeling index (0.95 ± 20 vs 1.02 ± 0.14, p=0.008) compared to the stable angina group. On the other hand, they had more lipid content (21.8 ± 7.03% vs 7.26 ± 3.47%, p=0.001), necrotic core (18.08 ± 10.19% vs 15.83 ± 4.9%, p=0.02), and calcifications (10.4 ± 5.2% vs 4.19 ± 3.29%, p=0.001) while less fibrosis (51.67 ± 7.07% vs 70.37 ± 11.7%, p=0.001) compared to the stable angina patients. Syntax score and core composition especially calcification and lipid content were significant predictors to NSTE-ACS. Conclusions. The vulnerability rather than the stenotic severity is the most important factor that predisposes to non-ST segment elevation acute coronary syndromes. The vulnerability is related to the lesion characteristics especially lipidic core and calcification while lesion fibrosis favours lesion stability.